Thionyl chloride battery based on solid active material solvation and preparation method thereof
Patent Information
- Application Number
- CN202610971895.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-13
AI Technical Summary
随着放电深度的增加,沉积的氯化锂形成致密绝缘层,覆盖碳颗粒表面并堵塞孔道,导致有效反应界面迅速减少,电极极化加剧、内阻显著上升,从而造成实际容量利用率偏低
[0022]本发明所具有的优点和积极效果是:
Smart Images

Figure CN122907577A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical power source technology, specifically relating to a thionyl chloride battery based on solid-state active material capacity enhancement and its preparation method. Background Technology
[0002] Lithium-thionyl chloride (Li / SOCl2) batteries are among the most commercially viable and mature primary battery systems, boasting advantages such as high operating voltage (approximately 3.6 V), high energy density (exceeding 500 Wh / kg), wide temperature range, and long storage life. They are widely used in smart water meters, electricity meters, medical equipment, oil exploration, and military equipment. However, the energy density improvement of traditional lithium-thionyl chloride batteries is gradually approaching the system's limit, with further development bottlenecks primarily focused on the cathode structure and its reaction mechanism. Current lithium-thionyl chloride batteries generally employ conductive carbon materials such as acetylene black as the cathode. Their main function is to provide an electron transport channel and serve as the reaction interface for the liquid-phase reduction reaction of thionyl chloride; however, the carbon material itself does not participate in Faraday-type redox reactions. Therefore, the traditional carbon material, which accounts for approximately 20%-30% of the mass and volume of the cathode, does not directly contribute to the electrochemical capacity, limiting further increases in the overall active material content of the battery.
[0003] Furthermore, the discharge process of lithium-thionyl chloride batteries follows a liquid reduction reaction mechanism, with its main discharge products including lithium chloride, elemental sulfur, and sulfur dioxide. Among these, lithium chloride is an electrically insulating substance and insoluble in the electrolyte, readily precipitating and accumulating in the micropores and surface of the carbon cathode during discharge. With increasing depth of discharge, the deposited lithium chloride forms a dense insulating layer, covering the carbon particle surface and blocking pores, leading to a rapid reduction in the effective reaction interface, intensified electrode polarization, and a significant increase in internal resistance, resulting in low actual capacity utilization. These problems are particularly pronounced under high-current or high-power discharge conditions, where lithium chloride more readily nucleates rapidly on the carbon cathode surface, forming a continuous deposition layer, causing premature passivation of the reaction region and severely limiting the battery's release capacity. On the other hand, to accommodate the large amount of insoluble products generated during discharge, traditional carbon cathodes typically need to maintain high porosity and large pore volume, which limits the loading of active material per unit volume, hindering further improvements in battery volumetric energy density. This problem is especially prominent for space- or volume-constrained electronic devices and integrated systems.
[0004] Therefore, how to overcome the inherent limitations of traditional carbon cathodes in terms of capacity contribution and reaction interface, introduce solid active materials that can directly participate in redox reactions, and simultaneously improve the specific capacity of the cathode while regulating the nucleation and deposition behavior of discharge products (such as lithium chloride), thereby achieving a simultaneous improvement in the energy density and capacity utilization of lithium-thionyl chloride batteries, has become an important technical problem that urgently needs to be solved in the field of chemical power sources. Contents of the Invention
[0005] The objective of the present invention is to provide a thionyl chloride battery with capacity enhancement based on solid active substances and a preparation method thereof.
[0006] To achieve the above objective, the technical solution adopted by the present invention is as follows: A thionyl chloride battery with capacity enhancement based on solid active substances, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is a composite positive electrode formed by introducing a solid material with intrinsic electrochemical capacity into a matrix; wherein the solid material with intrinsic electrochemical capacity is selected from one or more of a carbon fluoride material, a transition metal sulfide, a transition metal oxide, and a polyanionic positive electrode material, and the addition amount accounts for 10%-80% of the mass of the composite positive electrode.
[0007] The solid material with intrinsic electrochemical capacity introduced into the above composite positive electrode constructs a solid-liquid synergistic discharge composite positive electrode system, which undergoes deintercalation or conversion reaction with metal ions during the battery discharge process, so as to provide additional Faradaic capacity independent of the liquid-phase reduction reaction of thionyl chloride, breaking through the limitation that the traditional carbon positive electrode only serves as a reaction interface and does not contribute capacity; at the same time, it provides active sites for regulating the nucleation and deposition behavior of thionyl chloride discharge products, so as to alleviate pore blockage and interface passivation, and reduce polarization during the discharge process.
[0008] The carbon fluoride material is CF x , where 0<x ≤ 1.3; the transition metal sulfide is selected from at least one of FeS₂, CuS, MoS₂, and TiS₂; the transition metal oxide is selected from at least one of V₂O₅, MnO₂, Co₃O₄, Fe₂O₃, and MoO₃; the polyanionic positive electrode material is selected from at least one of LiFePO₄, Na₃V₂(PO₄)₃, Na₃V₂(PO₄)₂F₃ in a fully demetalized ion state (fully or partially demetalized ion state), transition metal phosphate (the transition metal is, for example, iron), pyrophosphate (e.g., iron salt) or sulfate (e.g., iron salt) materials.
[0009] The carbon fluoride material CF xThe cathode material possesses a high theoretical specific capacity and forms a conductive carbon phase after discharge, which can compensate in situ for the decrease in positive electrode conductivity caused by lithium chloride deposition. The transition metal sulfide material has a high volumetric energy density and can provide stable conversion capacity in the later stages of thionyl chloride discharge. Transition metal oxides or polyanionic cathode materials are also included. These materials can participate in solid-phase discharge during discharge through transition metal valence state changes or metal ion intercalation reactions, thus regulating and stabilizing the discharge voltage platform of the composite cathode. By introducing these substances, the cathode is transformed from a single "reaction site provider" into a "direct capacity contributor," significantly improving the total discharge capacity and energy density of the battery under the same volume conditions. Simultaneously, it optimizes the micro-reaction environment of the cathode, delays electrode passivation, and improves the actual utilization rate of thionyl chloride.
[0010] The composite positive electrode sheet is a composite positive electrode slurry loaded on a current collector; wherein, the composite positive electrode slurry, by mass percentage, consists of 10%-80% conductive agent, 10%-80% solid material with intrinsic electrochemical capacity, and the remainder is binder.
[0011] The conductive agent is at least one of acetylene black, Ketjen black, superconducting carbon black (Super P), graphite powder, carbon nanotubes (CNTs), vapor-grown carbon fibers (VGCF), or graphene. The adhesive is at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), or polyimide (PI).
[0012] The dispersion medium is water, anhydrous ethanol, isopropanol, N-methylpyrrolidone, etc.
[0013] A method for preparing a thionyl chloride battery based on solid-state active material capacity enhancement, as described above. (1) A solid material with intrinsic electrochemical capacity and a conductive agent are physically mixed, so that the solid material with intrinsic electrochemical capacity is loaded in the conductive agent, and then a binder and a dispersion medium are added to prepare a composite positive electrode slurry; (2) The composite positive electrode slurry is loaded onto the current collector, dried to remove the solvent, and rolled to obtain a composite positive electrode sheet; (3) Under inert atmosphere conditions, the metal negative electrode, separator and composite positive electrode are assembled and injected with thionyl chloride electrolyte, and the finished battery is obtained by sealing and aging.
[0014] The active component in the negative electrode is selected from lithium, sodium, potassium, calcium, magnesium, aluminum or their corresponding metal-based alloys. The metal-based alloys include, but are not limited to, one or more of lithium-aluminum alloys, lithium-silicon alloys, lithium-tin alloys, sodium-tin alloys, sodium-antimony alloys, potassium-tin alloys, magnesium-aluminum alloys and calcium-aluminum alloys.
[0015] The physical mixing method in step (1) is selected from at least one of ball milling, mechanical mixing, air jet milling or in-situ coating, so as to achieve fine dispersion of the solid material with intrinsic electrochemical capacity in the conductive agent.
[0016] The current collector can be selected from nickel mesh, stainless steel mesh, carbon paper, or other conductive substrates resistant to thionyl chloride corrosion.
[0017] The electrodes described above can be formed using either a dry or wet method.
[0018] To go even further: (1) Preparation of composite cathode slurry: Weigh solid materials with intrinsic electrochemical capacity and conductive agents according to the predetermined mass ratio; place the above solid powder in a dry or inert atmosphere and mix it by ball milling, mechanical stirring, air jet milling or other equivalent dispersion means so that the solid material (solid active material) is uniformly dispersed and embedded in the pore structure of the conductive agent (conductive carbon material) or coated on its surface; then add binder and appropriate amount of dispersion medium, stir thoroughly, and obtain uniform and stable cathode slurry.
[0019] (2) Forming and processing of positive electrode sheets: The positive electrode slurry is loaded onto the current collector by means of rolling, coating or pressing; the formed wet electrode sheet is placed in a vacuum oven or an inert atmosphere heating device and dried in stages or at a constant temperature within a temperature range of 60 ℃-200 ℃ to completely remove the dispersion medium and trace moisture; after drying, the positive electrode sheet is cut, rolled to densify and weighed and sorted, and then placed in a dry environment for later use.
[0020] (3) Negative electrode preparation and diaphragm selection: In a dry room with a dew point below -40 °C or a glove box protected by inert gas, the metal negative electrode is processed into a sheet, strip, or disc of a predetermined size and pressed or laminated onto the negative electrode current collector (or metal foil is used directly as the negative electrode); a glass fiber membrane, ceramic composite membrane, or porous fluororesin membrane that is resistant to thionyl chloride corrosion and has good ion permeability is selected and pre-treated by vacuum drying to remove water.
[0021] (4) Battery assembly and electrolyte injection: Following the stacking or winding sequence of "negative electrode-separator-composite positive electrode", each component is assembled into the battery casing (such as button, cylindrical, square or soft-pack structure); a thionyl chloride electrolyte containing conductive salt is injected into the battery casing, and the electrolyte is fully wetted into the microporous structure and solid active material interface inside the composite positive electrode by means of vacuum suction, centrifugal wetting or step-by-step liquid injection; after the sealing operation is completed, the battery is left to stand and age at room temperature for a certain period of time to eliminate internal polarization and form a stable solid-liquid electrochemical interface, thus obtaining the finished battery.
[0022] The advantages and positive effects of this invention are: This invention addresses the problems of traditional thionyl chloride batteries, where the carbon cathode serves only as a reaction interface without directly contributing capacity, and is prone to chloride deposition and blockage during discharge. It provides a method to introduce a solid-state material with intrinsic electrochemical capacity into a porous conductive carbon matrix, constructing a solid-liquid synergistic discharge composite cathode system. The introduced material can undergo an electrochemical reduction reaction within the battery's discharge potential window, providing Faraday capacity independent of the thionyl chloride liquid-phase reaction, and regulating the nucleation and deposition behavior of liquid-phase discharge products. Specifically: 1. This invention introduces a solid material with intrinsic electrochemical capacity into the carbon cathode of a thionyl chloride battery, transforming the cathode from an inert support that only provides a reaction interface into an active electrode that can directly contribute to the Faraday capacity, thereby significantly improving the battery's discharge specific capacity and energy density.
[0023] 2. The solid material with intrinsic electrochemical capacity introduced into the composite cathode constructed in this invention provides abundant heterogeneous nucleation sites, which can effectively regulate the growth morphology and deposition path of discharge products such as metal chlorides (e.g., LiCl), reduce cathode channel blockage and interface passivation, effectively alleviate voltage drop and voltage hysteresis, thereby significantly improving the high-current discharge performance and working stability of metal-thionyl chloride batteries.
[0024] 3. The capacity-enhancing composite cathode structure proposed in this invention has good universal adaptability to various types of metal anodes. It is not only applicable to lithium-thionyl chloride battery systems, but can also be extended to sodium and potassium alkali metal-thionyl chloride battery systems.
[0025] 4. The preparation method of the present invention is highly compatible with existing thionyl chloride battery production lines. The capacity enhancement effect can be achieved simply by adjusting the positive electrode ratio, without the need for complex modifications to the battery structure, and it has great potential for industrial application. Attached Figure Description
[0026] Figure 1 Example 1 and Comparative Example 1 are compared at 1 mA cm -2 Comparison of specific capacity-voltage curves under constant current discharge conditions; Figure 2 Example 5 is at 1mA cm -2 Comparison of specific capacity-voltage curves under constant current discharge conditions. Detailed Implementation
[0027] The following specific embodiments further illustrate the metal-thionyl chloride battery based on solid-state active material capacity enhancement according to the present invention. It should be noted that the following embodiments are only used to explain the technical solution of the present invention and do not constitute a limitation on the scope of protection of the present invention. Equivalent substitutions or modifications made by those skilled in the art without departing from the concept of the present invention should all fall within the scope of protection of the present invention.
[0028] This invention introduces a solid-state capacity-enhancing material with electrochemical reactivity into a traditional carbon cathode matrix, constructing a composite cathode system in which solid-liquid synergistic participation in the discharge reaction, thereby significantly improving the discharge capacity, energy density, and high-rate discharge performance of metal-thionyl chloride batteries. Simultaneously, it can effectively regulate the nucleation and deposition behavior of discharge products, delaying cathode passivation and voltage hysteresis, thus improving the battery's discharge performance and operational stability under high current. This invention is applicable to various metal-thionyl chloride systems, including alkali metals (lithium, sodium, potassium) and multivalent metals (calcium, magnesium, aluminum), and has good versatility and engineering application prospects.
[0029] Example 1 Lithium-thionyl chloride batteries with fluorinated carbon / carbon composite cathodes: Weigh out fluorinated carbon material CF x (x=0.9) and acetylene black were used as the positive electrode active material and conductive framework, respectively, and mixed at a mass ratio of 60:30; the mixture was then ball-milled for 6 h under a dry argon atmosphere to allow CF to... x The mixture was uniformly dispersed and loaded onto the pores and surface of carbon materials; then 10wt% PTFE emulsion was added as a binder and an appropriate amount of water, and the mixture was thoroughly stirred to obtain a uniform paste-like positive electrode slurry. The slurry was coated onto a stainless steel current collector to serve as a positive electrode sheet, and then dried at 150 °C for 24 h under vacuum to completely remove moisture and residual solvent. In an argon-protected glove box, a lithium metal sheet was used as the negative electrode, and a glass fiber membrane was selected as the separator material; the negative electrode, separator, and composite positive electrode were sequentially assembled into the battery casing, and an electrolyte containing 2 M LiAlCl4 thionyl chloride was injected into it; after encapsulation, the casing was left to stand and age at room temperature for 24 h.
[0030] Comparative Example 1 Traditional lithium-thionyl chloride batteries with pure carbon cathodes: 90 wt% acetylene black was used as the positive electrode conductive framework, 10 wt% PTFE emulsion was added as a binder and an appropriate amount of water, and the mixture was stirred evenly to obtain a slurry. This slurry was coated onto a stainless steel current collector and dried under vacuum at 150 °C for 24 h to obtain a conventional pure carbon positive electrode sheet. A coin cell was assembled using a lithium metal sheet as the negative electrode, glass fiber as the separator, and an electrolyte containing 2 M LiAlCl4 thionyl chloride.
[0031] The batteries assembled in Example 1 and Comparative Example 1 were subjected to constant current discharge tests, see [link to documentation]. Figure 1 The prepared battery exhibits a distinct dual-plateau discharge characteristic under constant current discharge conditions. Beyond the conventional thionyl chloride discharge plateau of around 3.6 V, a discharge plateau formed by CF4 appears in a lower voltage region. x The additional capacity plateau contributed by the first example is shown; while the Comparative Example 1 battery only exhibits a single liquid-phase depolarization discharge plateau of approximately 3.6 V. Polarization rapidly increases in the later stages of discharge, resulting in a precipitous drop in voltage, exhibiting the capacity decay characteristics caused by the dense deposition and blockage of the pores in the traditional carbon cathode by LiCl, and no secondary capacity-enhancing plateau was observed; whereas the introduction of CF in Example 1... x The battery assembled with the composite cathode has a total discharge capacity that is about 33% higher than that of Comparative Example 1, and its energy density is significantly improved.
[0032] Example 2 Lithium-thionyl chloride battery with FeS2 / carbon composite cathode: Nanoscale FeS2 powder and acetylene black were weighed and mixed at a mass ratio of 50:40, and mechanically mixed for 8 h in a dry environment. PVDF solution was added as a binder and NMP, and the mixture was stirred to obtain a uniform positive electrode slurry. The slurry was coated onto a stainless steel mesh and dried under vacuum at 120 ℃ for 20 h to obtain the FeS2 / carbon composite positive electrode sheet. A lithium metal sheet was used as the negative electrode, and glass fiber was selected as the separator. The electrolyte was a thionyl chloride electrolyte containing 2 M LiAlCl4. The battery was assembled and sealed in a conventional sequence.
[0033] During the constant current discharge process from 0.1 C to 1 C, FeS2 continues to undergo conversion reactions in the low-to-medium voltage region of this lithium-thionyl chloride battery, providing additional capacity to the system. Compared with traditional lithium-thionyl chloride batteries, the volumetric energy density and discharge capacity of the battery are significantly improved, while the voltage decay at the end of the discharge is effectively mitigated.
[0034] Example 3 Capacitance-enhanced lithium-thionyl chloride batteries based on pre-delithiated polyanion materials: Industrial-grade carbon-coated LiFePO4, conductive carbon black, and PVDF were mixed in a 90:5:5 mass ratio, and NMP was added and mixed thoroughly to obtain a uniform positive electrode slurry. This slurry was then processed onto a stainless steel current collector to obtain the positive electrode. Using this electrode as the positive electrode and a lithium metal sheet as the negative electrode, the electrode was charged to 4.0 V at a 0.1 C rate in a conventional ester electrolyte system (1.0 M LiPF6 in EC / DMC / DEC (volume ratio 1:1:1) solution) to fully convert LiFePO4 to delithiated FePO4. The electrode was then cleaned with dimethyl carbonate (DMC) in a dry environment and vacuum dried. The delithiated electrode (with the active material considered as FePO4) was used as one component of the composite positive electrode and mixed with acetylene black in a 50:50 mass ratio to prepare the composite positive electrode. In a glove box, using lithium metal as the negative electrode and a glass fiber diaphragm, an electrolyte containing 2 M LiAlCl4 containing thionyl chloride was injected to complete the assembly.
[0035] Under the test conditions of 1C constant current discharge to a cutoff voltage of 2.0 V, the results show that FePO4 particles act as heterogeneous nucleation centers in the porous carbon matrix. Their unique lattice structure and surface energy significantly reduce the deposition barrier of the discharge product LiCl, inducing LiCl to form a three-dimensional discrete island distribution on the surface of the active particles, rather than forming a dense, continuous coating film on the conductive carbon framework. This regulation of deposition morphology effectively maintains the ion transport channels inside the cathode and delays interface passivation. When the discharge enters the mid-to-late stages and the voltage drops below 3.4 V, FePO4 further releases capacity through a solid-phase lithium intercalation reaction, achieving a solid-liquid synergistic capacity enhancement through a reaction with thionyl chloride in the liquid phase. This results in a battery energy density increase of more than 20% compared to traditional pure carbon cathode batteries.
[0036] Example 4 Lithium-thionyl chloride battery with multi-component solid active material composite cathode: Weigh out the fluorinated carbon material CF according to a mass ratio of 40:20:30:10. x (x=0.9), vanadium pentoxide (V2O5), Ketjen Black conductive carbon, and PVDF binder. First, CF... x The active materials, V₂O₅ and V₂O₅, were subjected to composite ball milling under dry argon protection to ensure full contact and intercalation of the two materials at the microscale. Conductive carbon and isopropanol (a dispersant) were then added, and the mixture was subjected to high-speed shear stirring to form a homogeneous slurry. The slurry was coated onto a nickel mesh current collector and baked at 180 °C under vacuum for 24 h to obtain a multi-component composite positive electrode. In a glove box, a lithium metal sheet was used as the negative electrode, and a ceramic fiber composite separator was selected. A thionyl chloride electrolyte containing 2 M LiAlCl₄ and a small amount of aluminum stearate stabilizer was injected, and the battery was encapsulated using conventional processes.
[0037] Under test conditions of constant current discharge at 0.5C to a cutoff voltage of 2.0 V, the results show that this multi-component composite cathode achieves synergistic effects of graded discharge and kinetic compensation. This is because V₂O₅ operates at 3.2 V to 3.4 V (vs. Li / Li). + It exhibits good electrochemical activity within a certain range, and can rapidly relay discharge in the later stage of the thionyl chloride main reaction platform, providing not only additional Faraday capacity, but also its discharge product Li x The formation of V₂O₅ alters the energy level state of the cathode surface, further inducing discontinuous deposition of the liquid-phase product LiCl. In the later stages of discharge, relying on CF… x With its high specific capacity contribution and the heterogeneous nucleation sites it provides, the battery not only maintains a stable discharge platform, but also increases the total discharge capacity by more than 40% compared to the conventional pure carbon cathode in Comparative Example 1.
[0038] Example 5 Sodium-thionyl chloride battery with CuS / carbon composite cathode: Nano-copper sulfide (CuS) powder and Ketjen Black were weighed and mixed at a mass ratio of 80:10. The mixed powder was placed in a planetary ball mill and ball-milled at 300 rpm for 4 h under dry argon protection. High-energy ball milling was used to refine the CuS particles and highly disperse them within the micropores of Ketjen Black. Subsequently, 10 wt% PVDF binder and an appropriate amount of NMP were added, and the mixture was thoroughly stirred to prepare a high-solids content slurry. The slurry was uniformly coated onto carbon paper or nickel mesh current collector and dried in a vacuum oven at 120 ℃ for 12 h to obtain a CuS / carbon composite positive electrode. In a glove box, using a sodium metal sheet as the negative electrode and a corrosion-resistant porous polypropylene (PP) / ceramic composite separator, a conventional thionyl chloride electrolyte containing 2 M NaAlCl4 was injected into the battery system, and the battery was encapsulated using conventional processes.
[0039] Comparative Example 2 Traditional sodium-thionyl chloride batteries with pure carbon cathodes: The positive electrode preparation process is the same as that of Comparative Example 1. In an argon glove box, a sodium metal sheet is used as the negative electrode, glass fiber is used as the separator, and a thionyl chloride electrolyte containing 2 M NaAlCl4 is injected. The sodium-thionyl chloride battery is assembled according to conventional processes.
[0040] The batteries assembled in Example 5 and Comparative Example 2 were tested under the condition of constant current discharge at 0.2C to a cutoff voltage of 2.0V. Figure 2 As shown, the prepared battery exhibits a distinct dual-plateau discharge characteristic under constant current discharge conditions. Beyond the conventional thionyl chloride discharge plateau of around 3.1 V, CuS reaches a plateau at 2.0 V (vs. Na / Na). +The conversion reaction near CuS provides significant additional capacity. Due to the extremely high theoretical volumetric specific capacity of CuS, the volumetric energy density of this sodium-thionyl chloride battery is increased by approximately 30% compared to the conventional pure carbon cathode sodium-thionyl chloride battery in Comparative Example 2. Comparative Example 2 battery exhibits only a single liquid-phase discharge plateau of approximately 3.2 V-3.3 V. Due to the lack of heterogeneous nucleation sites, the discharge product sodium chloride (NaCl) rapidly forms a dense and continuous insulating passivation film on the carbon framework surface, leading to premature loss of the positive electrode active sites and a rapid drop in discharge voltage to the cutoff voltage. In this embodiment, the presence of CuS effectively induces discontinuous crystallization of the discharge product sodium chloride (NaCl) during discharge. Compared to the dense passivation layer formed by NaCl on the carbon surface in the Comparative Example, the NaCl in this embodiment tends to form loose particle clusters around CuS particles, preserving the electrolyte wetting channels inside the positive electrode. This allows the battery to maintain a low internal resistance even in the later stages of discharge, verifying the superior performance of this invention in the sodium-thionyl chloride system.
[0041] Example 6 Potassium-thionyl chloride battery with MnO2@C / carbon composite cathode: Manganese dioxide (MnO2) and high specific surface area conductive carbon black were weighed and mixed at a mass ratio of 70:20. To ensure close contact between the solid active material and the carbon skeleton, the mixed powder was wet-milled in anhydrous ethanol for 10 h and dried to obtain a composite powder. Subsequently, 10 wt% polytetrafluoroethylene (PTFE) dispersion was added as a binder, and the mixture was fiberized in a mixer, pressed into sheets, and cut into 14 mm diameter disc positive electrode sheets. The positive electrode sheets were placed in a vacuum oven and dried at 200 °C for 24 h to remove adsorbed water. In an argon glove box with water and oxygen content both below 0.1 ppm, using sliced potassium metal sheets as negative electrodes and a glass fiber separator, an electrolyte containing 1 M KAlCl4 thionyl chloride was injected into the battery. Assembly was completed according to the coin cell packaging process, and the battery was aged for 48 h to allow the electrolyte to fully wet the composite positive electrode.
[0042] Comparative Example 3 Traditional potassium-thionyl chloride batteries with pure carbon cathodes: The positive electrode preparation process is the same as that of Comparative Example 1. In an argon glove box, a sliced potassium metal sheet was used as the negative electrode, a glass fiber separator was selected, and a thionyl chloride electrolyte containing 1 M KAlCl4 was injected into the battery. The battery was then assembled into a potassium-thionyl chloride battery according to conventional processes.
[0043] Electrochemical performance tests of the batteries assembled in Example 6 and Comparative Example 3 under constant current discharge conditions of 0.1C to a cutoff voltage of 2.0 V showed that the potassium-thionyl chloride battery exhibited excellent discharge characteristics. The introduction of MnO2 provided abundant potassium intercalation sites, which were available at approximately 2.5 V-2.7 V (vs. K / K). + The potential range of MnO2 contributes significantly to the secondary discharge plateau. More importantly, since the MnO2 particles are uniformly distributed in the carbon framework, they act as heterogeneous nucleation centers, inducing the non-uniform growth of the discharge product potassium chloride (KCl). Experiments showed that KCl preferentially accumulates at the active sites of MnO2, effectively preventing the formation of a large-area interconnected insulating layer on the carbon surface, thereby significantly reducing the rate of increase in the battery's internal resistance. In contrast, the pure carbon cathode potassium-thionyl chloride battery (Comparative Example 3) exhibits a rapid increase in internal resistance during discharge due to the disordered accumulation of KCl products on the conductive carbon surface. Compared to Example 6, which contains MnO2 heterogeneous nucleation centers, the discharge plateau stability of this comparative example is poor, and the total discharge capacity is only about 65% of that of Example 6. This demonstrates the high feasibility of the solid-state active material capacity enhancement strategy described in this invention in potassium metal battery systems.
[0044] Example 7 CF x Magnesium-thionyl chloride battery with carbon composite cathode: Weigh CF x Mix CF and Kojic Black at a mass ratio of 70:20. Place the mixed powder in a planetary ball mill and ball mill for 6 hours under dry argon protection to achieve the desired CF content. x The PVDF binder was refined and highly dispersed within the micropores of porous carbon. Then, 10 wt% PVDF binder and an appropriate amount of NMP solvent were added, and the mixture was thoroughly stirred to prepare a high-solids-content slurry. The slurry was uniformly coated onto a nickel mesh current collector and dried in a vacuum oven at 150°C for 24 h to obtain CF. x / Carbon composite positive electrode. In an argon glove box with water and oxygen content both below 0.1 ppm, sliced magnesium metal sheets were used as the negative electrode, and a ceramic fiber composite separator was selected. A thionyl chloride electrolyte containing 1.5 M Mg(AlCl4)2 was injected into the battery. Assembly was completed according to the coin cell packaging process, and the battery was aged for 48 h to allow the electrolyte to fully wet the composite positive electrode.
[0045] Comparative Example 4 Traditional magnesium-thionyl chloride batteries with pure carbon cathodes: The positive electrode preparation process is the same as that of Comparative Example 1. In an argon glove box, a coin cell was assembled by injecting a thionyl chloride electrolyte containing 1.5 M Mg(AlCl4)2, using a magnesium sheet as the negative electrode and ceramic fiber as the separator.
[0046] The electrochemical performance of the batteries assembled in Example 7 and Comparative Example 4 was tested under a 0.1C constant current discharge condition. The results showed that the magnesium-thionyl chloride battery exhibited excellent discharge characteristics. Due to CF... x It exhibits excellent chemical stability in the thionyl chloride system, with no obvious gas evolution or corrosion observed. CF x The introduction of MgCl2 not only provides additional magnesium intercalation capacity, but more importantly, it effectively induces the discontinuous crystallization of the discharge product magnesium chloride (MgCl2) as a heterogeneous nucleation center. However, in the pure carbon cathode (Comparative Example 4), due to the lack of regulation by solid-state active materials, the discharge product MgCl2 forms a dense passivation layer on the conductive carbon surface during constant current discharge testing. 2+ The diffusion rate in the MgCl2 passivation layer is much lower than that in the lithium system, which leads to a rapid increase in battery polarization and an early drop in voltage to the cutoff voltage. However, the system in Example 7 effectively alleviates the rapid passivation caused by MgCl2, and the total discharge capacity is increased by more than 25% compared with Comparative Example 4, thus verifying the effectiveness of the present invention in solving the interface passivation problem in multivalent metal systems.
[0047] Meanwhile, the electrochemical performance of each embodiment and comparative example under constant current testing conditions is shown in Table 1.
[0048] Table 1. Summary of electrochemical performance parameters of the examples and comparative examples
[0049] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A thionyl chloride battery with capacity enhancement based on solid-state active material, comprising positive and negative electrodes, a separator, and an electrolyte, characterized in that: The positive electrode is formed by introducing a solid material with intrinsic electrochemical capacity into the matrix to form a composite positive electrode; wherein, the solid material with intrinsic electrochemical capacity is selected from one or more of fluorinated carbon materials, transition metal sulfides, transition metal oxides and polyanionic positive electrode materials; the amount added accounts for 10%-80% of the mass of the composite positive electrode.
2. The thionyl chloride battery based on solid-state active material capacity enhancement according to claim 1, characterized in that: The fluorinated carbon material is CF. x Where 0 < x ≤ 1.3; the transition metal sulfide is selected from at least one of FeS2, CuS, MoS2, and TiS2; the transition metal oxide is selected from at least one of V2O5, MnO2, Co3O4, Fe2O3, and MoO3; the polyanionic cathode material is selected from at least one of LiFePO4, Na3V2(PO4)3, Na3V2(PO4)2F3, transition metal phosphate, pyrophosphate, or sulfate materials in a completely demetallized state.
3. The thionyl chloride battery based on solid-state active material capacity enhancement according to claim 1, characterized in that: The composite positive electrode sheet is a composite positive electrode slurry loaded on a current collector; wherein, the composite positive electrode slurry, by mass percentage, consists of 10%-80% conductive agent, 10%-80% solid material with intrinsic electrochemical capacity, and the remainder is binder.
4. The thionyl chloride battery based on solid-state active material capacity enhancement according to claim 3, characterized in that: The conductive agent is at least one of acetylene black, Ketjen black, superconducting carbon black (Super P), graphite powder, carbon nanotubes (CNTs), vapor-grown carbon fibers (VGCF), or graphene. The adhesive is at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), or polyimide (PI).
5. A method for preparing a thionyl chloride battery based on solid-state active material capacity enhancement as described in claim 1, characterized in that, (1) A solid material with intrinsic electrochemical capacity and a conductive agent are physically mixed, so that the solid material with intrinsic electrochemical capacity is loaded in the conductive agent, and then a binder and a dispersion medium are added to prepare a composite positive electrode slurry; (2) The composite positive electrode slurry is loaded onto the current collector, dried and rolled to form a composite positive electrode sheet; (3) Under inert atmosphere conditions, the metal negative electrode, separator and composite positive electrode are assembled and injected with thionyl chloride electrolyte, and the finished battery is obtained by sealing and aging.
6. The method for preparing a thionyl chloride battery based on solid-state active material capacity enhancement according to claim 5, characterized in that, The active component in the negative electrode is selected from lithium metal, sodium, potassium, calcium, magnesium, aluminum, or their corresponding metal-based alloys.
7. The method for preparing a thionyl chloride battery based on solid-state active material capacity enhancement according to claim 5, characterized in that, The physical mixing method in step (1) is selected from at least one of ball milling, mechanical mixing, air jet milling or in-situ coating, so as to achieve fine dispersion of solid materials with intrinsic electrochemical capacity in conductive agent.